2002
DOI: 10.1111/1540-6237.00111
|View full text |Cite
|
Sign up to set email alerts
|

Elite Interlocks in Three U.S. Sectors: Nonprofit, Corporate, and Government

Abstract: This study traces elite interlocks between the economic, political, and civil sectors of the United States in the late 1990s. We assess integration and fragmentation through analyzing patterns of overlap and interaction among influential organizations and leaders in these sectors. Network analyses are conducted with UCINET 5 on the Elite Directors Database, a new data set composed of the directors/trustees for the largest organizations in the business and nonprofit sectors in addition to individuals holding po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…5 This sample includes the same 12 organizations studied by Burris (1992) and overlaps substantially with the samples analyzed by Burch (1983), Jenkins and Eckert (2000), Moore et al (2002), and Barnes (2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This sample includes the same 12 organizations studied by Burris (1992) and overlaps substantially with the samples analyzed by Burch (1983), Jenkins and Eckert (2000), Moore et al (2002), and Barnes (2006).…”
Section: Methodsmentioning
confidence: 99%
“…1 Moore, Sobieraj, Whitt, Mayorova, and Beaulieu (2002) analyzed board interlocks for 1997-98 within a sample of 100 large corporations and 109 nonprofit organizations, including 50 foundations, 47 charities, and 12 policy groups. They found large corporations to be the most heavily interlocked organizations, both among themselves and across institutional sectors, whereas nonprofit organizations (with the partial exception of policy groups) were relatively marginal to the inter-organizational network.…”
Section: Research On Non-corporate Interlocksmentioning
confidence: 99%
“…Only recently, scholars have begun to study the interlocks beyond the private sector with the public and civic sectors in a more systematic way (Moore, Sobieraj, Whitt, Mayorova, & Beaulieu, 2002;Salzman & Domhoff, 1983;Whitt & Lammers, 1991). Preliminary evidence of these studies suggests that non-profit organizations play a significant role as platforms of organized proximity between corporations and government advisory boards (Moore et al, 2003).…”
Section: Elite Network and The Interlocking Of Organizational Boardsmentioning
confidence: 99%
“…Additionally, Unseem (1984), in a study of corporate directors in the US and UK, demonstrated the key role held by an inner circle of directors with interlocking directorships in leading corporations and nonprofit boards. Moore, Sobieraj, Whitt, Mayorova, and Beaulieu (2002) extended this type of analysis and found three trends which affected the nonprofit sector in the US: "(1) the increased size of the sector, (2) the changing structure of nonprofit organizations and (3) the growing interpenetration between the state, the economy, and civil society" (2002, p. 729). They noted a blurring of the boundaries between the state, the market and civil society.…”
Section: Background: Network and Governance Of Corporations And Nonpmentioning
confidence: 99%
“…Moore et al (2002) explored whether certain types of nonprofit organizations were more tightly integrated than others with business leaders and concluded that substantial linkages existed across all types of nonprofit organizations.…”
Section: Background: Network and Governance Of Corporations And Nonpmentioning
confidence: 99%